High performance formic acid fuel cell benefits from Pd–PdO catalyst supported by ordered mesoporous carbon - Zhou, Yuan; Zhu, Xun; Zhang, Biao; Ye, Ding-Ding; Chen, Rong; Liao, Qiang (International journal of hydrogen energy, 2020)
Formic acid as a renewable fuel can be converted to clean electricity in fuel cells by high-efficient electrochemical oxidation. The conversion rate is fundamentally dictated by the synergy of interactive aspects: catalytic activity, accessibility to active sites, electron transfer, and anti-poisoning stability. For the first time, ordered mesoporous carbon (OMC) is used as the substrate for Pd–PdO catalyst for fuel cells. The unique ordered pore-channel network of OMC can enhance the spatial dispersion of Pd nanoparticles on the pore-channel wall, while the hollow pore-channel can facilitate reactant transport. Microwave and annealing treatments are found to enhance the chemical reduction and to strengthen the anchoring of Pd–PdO catalyst on OMC substrate, respectively. The OMC supported Pd–PdO catalyst (Pd–PdO/OMC) shows 1.7-fold and an order of magnitude higher mass activity and stability as compared to commercial Pd/C catalyst. For fuel cell testing, the Pd–PdO/OMC catalyst is applied to an air-breathing microfluidic fuel cell and achieves a maximum power density of 63.0 mW cm−2, at least one-fold higher than similar previous reports. •Ordered mesoporous carbon supported Pd-PdO catalyst was proposed.•The Ordered pore-channel network enhanced Pd dispersion and reactant transfer.•The as-prepared catalyst exhibited superior electrochemical performance for formic acid electro-oxidation.•The cell power density outperformed similar studies by 1-fold.